Thruway Branch Library. - Unknown (Forsyth County Public Library, 1960)
Photo made in the 1960s.
Thruway Branch Library. The branch closed June 29, 2002.
Keywords: Digital Forsyth; Winston-Salem (N.C.); Forsyth County Public Library; Forsyth County (N.C.) -- History -- Pictorial works; Forsyth County (N.C.) -- History -- Sources